2017
DOI: 10.1002/cnma.201700161
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Structural and Chemical Properties of Carbon Nano‐onions for Electrocatalysis

Abstract: Heteroatom doping of carbon nanostructures is a convenient tool to control their physicochemical properties and to make them suitable for various applications. Carbon nano‐onions (CNOs) doped with nitrogen (N‐CNOs) have been prepared by annealing aminated‐nanodiamond particles (AM‐NDs) at different temperatures (1150, 1450 and 1650 °C) in an inert He atmosphere. Their physicochemical properties were compared with those of pristine CNOs obtained from non‐functionalized NDs under the same experimental conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 52 publications
(101 reference statements)
0
28
0
Order By: Relevance
“…Nitrogen-doped CNOs (NÀ CNOs) have been prepared by annealing aminated-NDs (AM-NDs) at different temperatures (1,150, 1,450 and 1,650°C) in an inert He atmosphere. [150] HR-TEM investigations showed that NÀ CNOs have polygonal structures rather than spherical structures. This method allows for maintaining the π-conductive surface of CNOs, which is crucial for their applications in electrochemistry and electronics.…”
Section: Doping Of Cnos By Heteroatomsmentioning
confidence: 98%
See 4 more Smart Citations
“…Nitrogen-doped CNOs (NÀ CNOs) have been prepared by annealing aminated-NDs (AM-NDs) at different temperatures (1,150, 1,450 and 1,650°C) in an inert He atmosphere. [150] HR-TEM investigations showed that NÀ CNOs have polygonal structures rather than spherical structures. This method allows for maintaining the π-conductive surface of CNOs, which is crucial for their applications in electrochemistry and electronics.…”
Section: Doping Of Cnos By Heteroatomsmentioning
confidence: 98%
“…Boron‐doped CNOs (B‐CNOs) were obtained using an in situ method during electron irradiation of a graphitic material in a TEM and via chemical vapour deposition of BCl 3 and C 6 H 6 ,. The direct preparation of CNOs via thermal annealing of NDs using a boron source (H 3 BO 3 or amorphous powder of boron) or nitrogen was recently reported ,. A limited amount of boron species can be incorporated into the CNO structure (max.…”
Section: Doping Of Cnos By Heteroatomsmentioning
confidence: 99%
See 3 more Smart Citations